2010
DOI: 10.1371/journal.pcbi.1000838
|View full text |Cite
|
Sign up to set email alerts
|

Conductance Ratios and Cellular Identity

Abstract: Recent experimental evidence suggests that coordinated expression of ion channels plays a role in constraining neuronal electrical activity. In particular, each neuronal cell type of the crustacean stomatogastric ganglion exhibits a unique set of positive linear correlations between ionic membrane conductances. These data suggest a causal relationship between expressed conductance correlations and features of cellular identity, namely electrical activity type. To test this idea, we used an existing database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 39 publications
3
91
1
Order By: Relevance
“…Experimental and computational studies suggest that distinct conductance ratios are maintained in identified pyloric neurons, including the ratio of LP I A to I h (Schulz et al, 2006(Schulz et al, , 2007Hudson and Prinz, 2010), and modulators are necessary for their maintenance (Khorkova and Golowasch, 2007). Interestingly, steadystate DA also regulates LP I A G max (Rodgers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and computational studies suggest that distinct conductance ratios are maintained in identified pyloric neurons, including the ratio of LP I A to I h (Schulz et al, 2006(Schulz et al, , 2007Hudson and Prinz, 2010), and modulators are necessary for their maintenance (Khorkova and Golowasch, 2007). Interestingly, steadystate DA also regulates LP I A G max (Rodgers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Modeling work in the pyloric network of the crustacean STN has suggested that, rather than connection strengths, it may be their ratios that are important in network function (Hudson and Prinz 2010). The importance of synaptic ratios is supported by the data presented here, where there is substantial variability in connection strengths among individuals, but there do appear to be some points (that we can measure and accurately compare) where the balance (ratio) of the two synapses appears to be maintained as indicated by significant correlations [for example, the HN(2) to HN(4) connection compared with the HN(4) to HN(4) connection or the HN(5) to HN(7i) connection compared with the HN(3) to HN(7) connection (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This puzzle was resolved by the finding that the overexpression of I A was accompanied by a compensating up-regulation of the hyperpolarization-activated inward current (I H ) (38,41). Interestingly, strong correlations in the expression of I A and I H mRNA are also seen in crab STG neurons (11,20,25), and it has been suggested that the specific patterns of correlations seen in identified neurons may be a signature of their identity (25,26,42,43). …”
Section: Parameter Compensation and Correlationsmentioning
confidence: 99%